2016
DOI: 10.1093/jscr/rjw074
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Dieulafoy's lesion: an exceedingly rare cause of massive upper GI bleeding

Abstract: Dieulafoy's lesion, a dilated aberrant submucosal vessel which erodes the overlying epithelium, is a relatively rare but potentially fatal cause of gastrointestinal (Gl) bleeding. The esophagus is a very rare location for the lesion. Here we present a case of massive upper GI bleeding, secondary to this remarkably rare occurrence, which was amendable to endoscopic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Delay in the diagnosis and inadequate management due to the lack of clinical familiarity make the Dieulafoy's lesion a stealth killer 5 25. Goldman review of 24 cases reported 19 deaths which give mortality as high as 80%, highlighting the urgent diagnosis and management of the lesion 26…”
Section: Discussionmentioning
confidence: 99%
“…Delay in the diagnosis and inadequate management due to the lack of clinical familiarity make the Dieulafoy's lesion a stealth killer 5 25. Goldman review of 24 cases reported 19 deaths which give mortality as high as 80%, highlighting the urgent diagnosis and management of the lesion 26…”
Section: Discussionmentioning
confidence: 99%
“…It may be that this process is multifactorial, including disruption in the mucosal epithelium secondary to pulsations in the abnormally large submucosal vessel. Age, insults, and illness may also contribute, as DLs in adults have been correlated with comorbidities including cardiovascular disease, hypertension, chronic renal disease, diabetes mellitus, and excessive alcohol abuse . However, in most pediatric cases, including ours, these comorbidities are noncontributory.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate has dropped from 80% to 8.6% since endoscopy has been employed in the identification of causes in GI bleeds, and it has been reported to be effective in more than 90% of patients. Endoscopy has 70% sensitivity, and if it fails to diagnose the lesion, angiography can be used to embolise the lesion 3. Giles et al reported TC-325 also known as Hemospray can be used as a rescue therapy when haemostasis cannot be achieved using standard interventions and as the first line in cases of diffuse bleeding that cannot be controlled using the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-day rebleeding was significantly lower with Doppler-guided endoscopic haemostasis compared with standard visually guided haemostasis in patients with severe upper GI haemorrhage from ulcers or other lesions 20. If minimally invasive approaches fail, surgery is reserved as a last resort 3. Although a Dieulafoy’s lesion is exceedingly rare in the oesophagus, it is associated with a high mortality if undiscovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation